The role of TV news exposure in Metro Manila residents' perceived legitimacy of the Philippine criminal justice system and their willingness to participate in the criminal justice system - Buston, Joan B.; Cruz, Marinella Rosette R.
Previous studies on legitimacy, a trait of institutions defined as "right to exercise power" (Tankebe, 2013, p.1), suggest that it can encourage behavior from citizens. Using the Cultivation Theory and the Theory of Planned Behavior, this study examines how TV news exposure influences Metro manila residents' perceived legitimacy of and their willingness to participate in the Philippine Criminal Justice System. Based on data from 395 survey respondents, this study finds exposure to TV news influences Metro Manila residents' perceived legitimacy of the CJS. Consequently, perceived legitimacy is not the strongest predictor of willingness to participate in the CJS as statistical modeling results indicate perception of participation in the system as the strongest independent variable. Moreover, TV news exposure does not encourage participation in the CJS, implying that participation in the CJS among Metro Manila residents is more dependent on factors involving personal opinions than those which rely on other sources of information, such as referents and the media.